2020
DOI: 10.1111/jipb.12903
|View full text |Cite
|
Sign up to set email alerts
|

COP9 signalosome: Discovery, conservation, activity, and function

Abstract: The COP9 signalosome (CSN) is a conserved protein complex, typically composed of eight subunits (designated as CSN1 to CSN8) in higher eukaryotes such as plants and animals, but of fewer subunits in some lower eukaryotes such as yeasts. The CSN complex is originally identified in plants from a genetic screen for mutants that mimic light-induced photomorphogenic development when grown in the dark. The CSN complex regulates the activity of cullin-RING ligase (CRL) families of E3 ubiquitin ligase complexes, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 109 publications
(163 reference statements)
0
63
1
Order By: Relevance
“…Upon light exposure, light signals and light-activated photoreceptors inhibit COP/DET/FUS activity through multiple molecular regulatory mechanisms (Hoecker, 2017;Podolec and Ulm, 2018). COP/DET/FUS proteins consist of three distinct biochemical entities: the COP1-SPA complex, the COP10-DET1-DNA DAMAGE BINDING PROTEIN1 (DDB1; CDD) complex, and the COP9 signalosome (CSN; Wei and Deng, 2003;Yanagawa et al, 2004;Zhu et al, 2008;Qin et al, 2020). The Arabidopsis genome encodes four SPA proteins (SPA1 to SPA4), and two COP1 and two SPA proteins form a stable core complex (Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Upon light exposure, light signals and light-activated photoreceptors inhibit COP/DET/FUS activity through multiple molecular regulatory mechanisms (Hoecker, 2017;Podolec and Ulm, 2018). COP/DET/FUS proteins consist of three distinct biochemical entities: the COP1-SPA complex, the COP10-DET1-DNA DAMAGE BINDING PROTEIN1 (DDB1; CDD) complex, and the COP9 signalosome (CSN; Wei and Deng, 2003;Yanagawa et al, 2004;Zhu et al, 2008;Qin et al, 2020). The Arabidopsis genome encodes four SPA proteins (SPA1 to SPA4), and two COP1 and two SPA proteins form a stable core complex (Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the discovery of drugs targeting allergic diseases, phytochemicals have taken an important part such as galangin (16), chrysin (17) and chicoric acid (18). As the major phytochemical, irisflorentin was found in Belamcanda chinensis (9) and Iris leptophylla Lingelsh (10). Pharmacokinetic analysis has revealed after oral administration of irisflorentin 27.0 mg/kg in Belamcanda chinensis extract to rats, the maximum plasma concentration (C max ) was 29.9 ± 3.5 ”g/mL, time to maximum concentration (T max ) was 0.25 ± 0.0 h, apparent elimination half-life time (t 1/2 ) was 3.48 ± 0.37 h, and area under the curve (AUC) was 52.42 ± 5.7 ”g/Lh (19).…”
Section: Discussionmentioning
confidence: 99%
“…CELLS VIA REDUCING HISTAMINE RELEASE AND PRODUCTION OF PRO-INFLAMMATORY CYTOKINES Irisflorentin (Fig. 1) is an isoflavonoid found in Belamcanda chinensis (9) and Iris leptophylla Lingelsh (10). Previous pharmacological investigations have shown irisflorentin affords neuroprotection (11) and anti-inflammation (12).…”
Section: Irisflorentin Suppresses Allergic Inflammation In Mastmentioning
confidence: 99%
“…During these two distinct developmental processes, a variety of biological factors, including multiple photoreceptors, E3 ubiquitin ligases, and transcriptional regulators, work in concert to determine the response to changing light conditions in plants (Lin and Wang. 2007;Quail 2007;Zhang et al 2007;Xu 2019;Qin et al 2020). Extensive studies have shown that BBXs act as transcription factors or transcriptional regulators and that they work in parallel and coordinate with other factors in light-controlled seedling development (Table 1, Figure 2).…”
Section: Involvement Of Bbx In the Regulation Of Photomorphogenesismentioning
confidence: 99%